On the validity of the autobiographical emotional memory task for emotion induction. - Caitlin Mills; Sidney D'Mello (PLoS ONE)
The Autobiographical Emotional Memory Task (AEMT), which involves recalling and writing about intense emotional experiences, is a widely used method to experimentally induce emotions. The validity of this method depends upon the extent to which it can induce specific desired emotions (intended emotions), while not inducing any other (incidental) emotions at different levels across one (or more) conditions. A review of recent studies that used this method indicated that most studies exclusively monitor post-writing ratings of the intended emotions, without assessing the possibility that the method may have differentially induced other incidental emotions as well. We investigated the extent of this issue by collecting both pre- and post-writing ratings of incidental emotions in addition to the intended emotions. Using methods largely adapted from previous studies, participants were assigned to write about a profound experience of anger or fear (Experiment 1) or happiness or sadness (Experiment 2). In line with previous research, results indicated that intended emotions (anger and fear) were successfully induced in the respective conditions in Experiment 1. However, disgust and sadness were also induced while writing about an angry experience compared to a fearful experience. Similarly, although happiness and sadness were induced in the appropriate conditions, Experiment 2 indicated that writing about a sad experience also induced disgust, fear, and anger, compared to writing about a happy experience. Possible resolutions to avoid the limitations of the AEMT to induce specific discrete emotions are discussed.